The clinical course of interstitial lung disease in an adult patient with an ABCA3 homozygous complex allele under hydroxychloroquine and a review of the literature: ABCA3 mutations and hydroxychloroquine - Legendre, Marie; Darde, Xavier; Ferreira, Marion; Chantot-Bastaraud, Sandra; Campana, Marion; Plantier, Laurent; Nathan, Nadia; Amselem, Serge; Toutain, Annick; Diot, Patrice; Marchand-Adam, Sylvain (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2022)
The gene mutations responsible for ABCA3 protein deficiency are involved in respiratory distress of the newborn and much more rarely in adult interstitial lung diseases (ILD). An adult patient homozygous for a complex allele encompassing the p.Ala1027Pro likely pathogenic mutation and the p.Gly974Asp variation was followed for a late-onset and fibrotic ILD. The evolution was marked by progressive clinical and functional degradation despite corticosteroid pulses. The patient, who was first registered on the list for lung transplantation, was improved quickly and persistently for at least 6.5 years with hydroxychloroquine treatment, allowing removal from the transplant list.